Genetic damage in New Zealand Vietnam War veterans : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Genetics at Massey University, Palmerston North, New Zealand - Edwards, Louise Ann (Massey University, 2006)
From July 1965 until May 1971, New Zealand Defence Force Personnel fought in the Vietnam War. During this time the United States military forces sprayed more than 76,500,000 litres of phenoxylic herbicides over parts of Southern Vietnam and Laos. The most common herbicide sprayed was known as 'Agent Orange'. All of the Agent Orange sprayed during the Vietnam War was contaminated with 2,3,7,8- tetrachlorobenzo-para-dioxin (known simply as TCDD), a known human carcinogen. Since returning to New Zealand more than 30 years ago, New Zealand Vietnam War veterans have expressed concern about the numerous health problems experienced by both themselves and their children. New Zealand Vietnam War veterans attribute these health problems to exposure to Agent Orange while serving in Vietnam. This study aimed to ascertain whether or not New Zealand Vietnam War veterans have incurred genetic damage as a result of service in Vietnam. The Sister Chromatid Exchange assay (SCE) is a very sensitive and widely applied assay used to detect genetic damage induced by an environmental agent or clastogen. In the current study a group of New Zealand Vietnam War veterans and a control group were compared using an SCE analysis in order to determine if genetic damage had been sustained by the Vietnam War veterans. All participants were screened to reduce the possible influence of factors that could severely impact on findings and to eliminate any bias in the SCE results. The results from the SCE study show a highly significant difference between the mean of the experimental group and the mean of the control group (p < 0.001). This result indicates that New Zealand Vietnam War veterans have sustained genetic damage; this damage can be attributed to service in Vietnam (possibly as a result of exposure to Agent Orange). This result is strong and indicates that further scientific research on New Zealand Vietnam War veterans is required.
Accompanying CD-ROM contains the complete SCE results for all participants System requirement Microsoft Excel
Keywords: New Zealand; Vietnam War, 1961-1975 -- Veterans; Human chromosome abnormalities